Power Law Distribution in Electric Power Data - Guannan Wang; Chunyu Deng; Yue Zhao; Yaqin Zheng (Dianxin kexue)
The explorative analysis plays an important role in the process of data mining. The non-normally distributed data in the electric power data was analyzed. Firstly,the distribution law of generated energy, electricity sales and electricity consumption with statistical methods across the province within the business area of SGCC were analyzed, and it was found that these indices were not normally distributed but follow the power law distribution. Then the electricity consumption of subdivided trade follows the log-normal distribution was proved. At last, the reasons that these data are not normally distributed were given.